Impact of tradicional and non-traditional pre-sports games in the perceived and observed motor competence of costarican school children - Salazar-Cruz, Pamela (2024)
Concerning variables such as perceived and observed motor competence (PMC and OMC respectively), research has been done on how motor interventions can cause positive effects. However, the effects of non-traditional pre-sports games (in the Costa Rican milieu) have been scarcely studied. This research intended to determine the effect of traditional (T) and non-traditional (NT) pre-sports games on PMC and OMC in Costa Rican elementary school children. Participants included 72 fourth-grade students from two Costa Rican public primary schools. The control group did not undergo any treatment, while the experimental groups were randomly assigned to the following treatments: T, NT and mixed (T and NT), and each of the 3 groups carried out 7 80-minute sessions, once a week. PMC was assessed by using the Pictographic Scale of Perceived Competence in Motor Skills for Young Children, and OMC was assessed with the Test for Gross Motor Development (TGMD-2). It was found that all three experimental groups improved significantly (between measurements) in object handling skills, as compared to the control group (F = 10.75; p = .001). As to the other variables, no statistically significant differences (p > .05) were observed among groups and measurements. The conclusion is that a T or NT program, or the combination of both, foster significant improvements in the handling skills observed in this population of fourth-grade primary school students. It is recommended that these types of activities be introduced in Physical Education classes.